2017
DOI: 10.1001/jama.2017.17924
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High-Cutoff Hemodialysis vs Conventional Hemodialysis on Hemodialysis Independence Among Patients With Myeloma Cast Nephropathy

Abstract: clinicaltrials.gov Identifier: NCT01208818.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
150
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(160 citation statements)
references
References 38 publications
6
150
1
3
Order By: Relevance
“…6,7 A randomized controlled study, called MYRE, showed that FLCs removal with a HCO dialyzer improves patients' outcomes. 8 However, high cost, elevated protein leakage requiring albumin replacement after treatments reduce its utilization. 7 As a consequence dialyzers cheaper than HCO dialyzers, efficient in FLCs removal but without protein leakage are still wanted.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 A randomized controlled study, called MYRE, showed that FLCs removal with a HCO dialyzer improves patients' outcomes. 8 However, high cost, elevated protein leakage requiring albumin replacement after treatments reduce its utilization. 7 As a consequence dialyzers cheaper than HCO dialyzers, efficient in FLCs removal but without protein leakage are still wanted.…”
Section: Discussionmentioning
confidence: 99%
“…Cast nephropathy is generated by massive light chain secretion in the tubules and precipitated with reduction of tubular flow. There was an RCT comparing between intensive HD (eight 5-hour sessions over 10 days) with a HCO dialyzer (HCO-HD) and conventional HD among patients who were newly diagnosed with myeloma cast nephropathy and treated with a bortezomib-based chemotherapy regimen [44]. HCO-HD allowed higher clearance of both kappa (κ) and lambda (λ) light chains.…”
Section: Hdf and Myeloma Cast Nephropathymentioning
confidence: 99%
“…High‐cut‐off membranes and the new generation medium cut‐off membranes may potentially have a role in the management of light nephropathy along with appropriate chemotherapy. However, the actual reported clinical outcomes using these high cut‐off membranes remain inconclusive …”
Section: Dialyzer Choice In Aki and In Critical Carementioning
confidence: 99%
“…However, the actual reported clinical outcomes using these high cut-off membranes remain inconclusive. 3,[82][83][84]…”
Section: S69mentioning
confidence: 99%